Transformation of Indian automobile industry through inter-organization IT initiative : AutoDX (A) - Verma, Sanjay, (SAGE Business Cases., 2018)
The case centres on the 2015 common data exchange, an initiative for all automobile manufactures in India to share data. Part A of the case series examines the practicality and difficulty of implementing such a system and the potential benefits.